Aeromonas spp. as possible bacterial indicator for monitoring antibiotic resistance in seafood - Albini, Elisa; Caponi, Biagio; Pieralisi, Silvia; Orsini, Serenella; Blasi, Francesca; Massaccesi, Luisa; Maresca, Carmen; Scoccia, Eleonora; Fiorucci, Alessandro; Michelacci, Valeria; Chiani, Paola; Marra, Manuela; et al. (Frontiers in Microbiology, 2026)
Fishery and aquaculture products increasingly represent an important food source for the world population. The intensification of aquaculture guided an increase in the use of antimicrobials in this sector as well. The aquatic environment represents a link among humans, animals and environmental antibiotic resistance. The rising problem of antibiotic resistance leads to the need for the identification of indicator bacteria and the development of monitoring methods, which are poorly standardized for the aquatic environment. Aeromonas spp., a ubiquitous bacterium in aquatic environments, is among the possible candidates as bacterial indicator. The goals of this study were to: (i) evaluate the antibiotic-resistance profile of different antimicrobial classes in Aeromonas spp. collected from seafood sold in superstores of central Italy; (ii) propose possible epidemiological cut-offs for the genus Aeromonas and evaluate its effectiveness as a possible bacterial indicator for monitoring antibiotic resistance in seafood. The results obtained revealed a high presence of Aeromonas spp. in seafood categories, highlighting its candidature as a bacterial indicator. The presence of isolates resistant to some of the tested antibiotics has been described, even if in rare occasion. This data raises concerns about the food safety of seafood for consumption, which may represent a risk for public health and consumers. In this study, we described the epidemiological cut-offs which agree with the literature, representing a contribution to the definition of reliable epidemiological cut-offs for the genus Aeromonas spp.